Acibenzolar-S-Methyl Activates Stomatal-Based Defense Systemically in Japanese Radish - Sakata, Nanami; Ishiga, Takako; Taniguchi, Shizuku; Ishiga, Yasuhiro (Frontiers in Plant Science, 2020)
Acibenzolar-S-methyl (ASM) is a well-known plant activator, which is a synthetic analog of salicylic acid (SA). Recently, copper fungicides and antibiotics are major strategies for controlling bacterial diseases. However, resistant strains have already been found. Therefore, there is an increasing demand for sustainable new disease control strategies. We investigated the ASM disease control effect against Pseudomonas cannabina pv. alisalensis (Pcal), which causes bacterial blight on Japanese radish. In this study, we demonstrated that ASM effectively suppressed Pcal disease symptom development associated with reduced bacterial populations on Japanese radish leaves. Interestingly, we also demonstrated that ASM activated systemic acquired resistance (SAR), including stomatal-based defense on ASM-untreated upper and lower leaves. Reactive oxygen species (ROS) are essential second messengers in stomatal-based defense. We found that ASM induced stomatal closure by inducing ROS production through peroxidase. These results indicate that stomatal closure induced by ASM treatment is effective for preventing Pcal pathogen invasion into plants, and in turn reduction of disease development.